Comparative effects of telephone versus in-office behavioral counseling to improve HIV treatment outcomes among people living with HIV in a rural setting. Issue 3 (17th November 2020) - Kalichman, Seth C; Katner, Harold; Eaton, Lisa A; Banas, Ellen; Hill, Marnie; Kalichman, Moira O
Abstract: With the expansion of telehealth services, there is a need for evidence-based treatment adherence interventions that can be delivered remotely to people living with HIV. Evidence-based behavioral health counseling can be delivered via telephone, as well as in-office services. However, there is limited research on counseling delivery formats and their differential outcomes. The purpose of this study was to conduct a head-to-head comparison of behavioral self-regulation counseling delivered by telephone versus behavioral self-regulation counseling delivered by in-office sessions to improve HIV treatment outcomes. Patients ( N = 251) deemed at risk for discontinuing care and treatment failure living in a rural area of the southeastern USA were referred by their care provider. The trial implemented a Wennberg Randomized Preferential Design to rigorously test: (a) patient preference and (b) comparative effects on patient retention in care and treatment adherence. There was a clear patient preference for telephone-delivered counseling (69%) over in-office-delivered counseling (31%) and participants who received telephone counseling completed a greater number of sessions. There were few differences between the two intervention delivery formats on clinical appointment attendance, antiretroviral adherence, and HIV viral load. Overall improvements in health outcomes were not observed across delivery formats. Telephone-delivered counseling did show somewhat greater benefit for improving depression symptoms, whereas in-office services demonstrated greater benefits for reducing alcohol use. These results encourage offering most patients the choice of telephone and in-office behavioral health counseling and suggest that more intensive interventions may be needed to improve clinical outcomes for people living with HIV who may be at risk for discontinuing care or experiencing HIV treatment failure.